2021
DOI: 10.1371/journal.pone.0249108
|View full text |Cite
|
Sign up to set email alerts
|

Integrating transcriptome and metabolome analyses of the response to cold stress in pumpkin (Cucurbita maxima)

Abstract: Cucurbita maxima belong to the genus Cucurbita and are of nutritional and economic importance. Physiological activity, transcriptome, and metabolome analyses of leaf samples from the C. maxima inbreding line IL7 treated at 5 °C and 25 °C were performed. Cold stress resulted in a significant increase in the malondialdehyde content, relative electrical conductivity, soluble protein, sugar content, and catalase activity. A total of 5,553 differentially expressed genes were identified, of which 2,871 were up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 91 publications
1
9
0
Order By: Relevance
“…Low temperature is one of the common abiotic stresses affecting plant growth. Plants adapt to low temperatures by changing their morphology and adjusting the expression of a series of genes involved in complex networks ( Lantzouni et al., 2020 ; Li et al., 2021a ). As an interesting phenotype response to chilling stress, leaves color changes have been concerned in many previous studies ( Ahmed et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low temperature is one of the common abiotic stresses affecting plant growth. Plants adapt to low temperatures by changing their morphology and adjusting the expression of a series of genes involved in complex networks ( Lantzouni et al., 2020 ; Li et al., 2021a ). As an interesting phenotype response to chilling stress, leaves color changes have been concerned in many previous studies ( Ahmed et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The WRKY transcription factor family plays a role in plant response to abiotic stresses such as cold and drought [ 16 , 38 ]. In this research, WRKY48 was upregulated in grafted cucumbers from both rootstocks, suggesting that WRKY48 expression may be influenced by the rootstock and is positively correlated with cold tolerance in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism and a range of redox processes are reported to play a significant role in the response of crops to cold stress [ 14 ]. Lipid metabolism, including membrane lipid and fatty acid metabolism, highly influences the response to cold stress [ 15 , 16 ]. Phenylpropanoid metabolism [ 17 ], phytohormone signaling [ 18 ], and transcription factors [ 19 ] have also been reported to regulate cold tolerance in crops.…”
Section: Introductionmentioning
confidence: 99%
“…Omics studies in other plants have revealed the involvement of multiple pathways in protecting plant leaves from cold injury. For example, a combined metabolome and transcriptome study in Cucurbita maxima showed that genes related to phytohormone signaling, carbohydrate metabolism, amino acid metabolism, phenylpropanoid pathway are highly expressed in the cold tolerant genotype [ 16 ]. Whereas in Capsicum annum, metabolome analysis revealed differential accumulation of phytohormones, polyamines and osmolytes along with increased expression of genes related to calcium, MAPK, phytohormone and reactive oxygen species (ROS) signaling [ 17 ].…”
Section: Introductionmentioning
confidence: 99%